Acquisitions of German companies by Chinese and Indian corporations – a threat to employment and knowledge retention? - Bollhorn, Kai (DIE ERDE – Journal of the Geographical Society of Berlin, 2015)
The economies of China and India have grown rapidly in the last decades. This also fosters the internationalisation of domestic market companies. Unlike corporations from the Triad (USA, Europe, Japan), Chinese and Indian enterprises acquire existing companies in developed economies rather than follow the greenfield investment route. While a lot of research has gone into explaining this behaviour, the consequences for the acquired companies have hardly been examined. The few existing studies highlight a substantial potential threat for the targeted firms. Based on qualitative, semi-structured interviews with German companies acquired by Chinese or Indian companies and experts, this study arrives at the result that these investments do not pose a threat to the German companies. This study takes an opposite position to existing publications. The global production networks (GPN) approach is used as an analytical framework for this study.